Learning from Home Behavior: Looking beyond Learning Opportunity and Non-opportunity - Kanyawee Duangpim; Pornchita Khamhueng; Athittaya Kaewpikul; Prasart Nuangchalerm (Gagasan Pendidikan Indonesia, 2021)
This study employed survey research, aims to investigate students’ opinion towards online learning environment which make opportunity and non-opportunity in learning achievement. The research gathered data from 224 secondary students from one school in academic year 2021, located in Roi-et Province, Thailand. Questionnaire was made and asked about learning from home behavior during COVID-19 pandemic. Statistics used for data analysis consisted of mean and standard deviation. This research showed that learning from home behaviors of secondary students had moderate levels in all dimension. The guideline of curriculum and learning management, learning opportunity, and barriers in distance learning should be considered. Educational policy should be discussed how to do the suitable things to support schools based on needs and appropriate solutions.